Tinjauan Terhadap Strategi Pemasaran Inovatif Dalam Pengembangan Usaha Kewirausahaan - Fachri Habib; Dita Oktaviani; Nurul Adinda Lubis (Jurnal Publikasi Ilmu Manajemen, 2024)
Marketing strategy and product innovation have a positive and significant influence on the marketing performance of micro, small and medium enterprises (MSMEs) in various cities in Indonesia. When implementing innovative marketing strategies, entrepreneurs must pay attention to good management and organizational skills to achieve business goals. Apart from that, budget control is also an important factor in developing entrepreneurial ventures.When developing an entrepreneurial venture, entrepreneurs must consider innovative marketing strategies and proper budget management to achieve their business goals.